Preclinical efficacy and safety of the Ty21a vaccine strain for intravesical immunotherapy of non-muscle-invasive bladder cancer. (2nd January 2017) - Domingos-Pereira, Sonia; Cesson, Valérie; Chevalier, Mathieu F.; Derré, Laurent; Jichlinski, Patrice; Nardelli-Haefliger, Denise
ABSTRACT: Intravesical Bacillus-Calmette-Guérin (BCG) immunotherapy can reduce recurrence/progression of non-muscle-invasive bladder cancer (NMIBC), although significant adverse events and treatment failure argue for alternative options. Here, we examined whether another attenuated live vaccine, Vivotif/Ty21a, used since more than 30 y against typhoid fever, may be safely used intravesically to improve bladder-tumor treatment. Mice-bearing MB49 orthotopic bladder-tumors treated with intravesical Ty21a or BCG were compared for survival and bacteria recovery. Both Ty21a and BCG enhanced mice survival when treating just after tumor implantation for 4 weeks ( p = 0.008 and 0.04, respectively), but only Ty21a was effective when treating once mice with larger already established bladder-tumors ( p = 0.0003). In contrast to BCG, no Ty21a bacteria survived in mouse bladder, human urothelial cell-lines or human peripheral blood mononuclear cells. However, Ty21a was as potent as BCG to induce tumor-cell death in vitro . In a human, 3D-bladder-tissue ex-vivo assay, Ty21a bacteria, still not surviving, induced a panel of cytokines associated with effective BCG-treatment in patient's urine. Overall, our pre-clinical data demonstrate that intravesical Ty21a is more effective than BCG for bladder-tumor treatment. Absence of surviving Ty21a bacteria and the excellent safety-record of the typhoid vaccine support its testing in NMIBC patients.